2014
DOI: 10.2147/dddt.s64940
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical profile of cabazitaxel

Abstract: First-generation taxanes have changed the treatment paradigm for a wide variety of cancers, but innate or acquired resistance frequently limits their use. Cabazitaxel is a novel second-generation taxane developed to overcome such resistance. In vitro, cabazitaxel showed similar antiproliferative activity to docetaxel in taxane-sensitive cell lines and markedly greater activity in cell lines resistant to taxanes. In vivo, cabazitaxel demonstrated excellent antitumor activity in a broad spectrum of docetaxel-sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 61 publications
1
50
0
Order By: Relevance
“…Cabazitaxel is a semisynthetic taxane that was identified through a large‐scale screening process designed to select agents that show consistent activity in both docetaxel‐sensitive and docetaxel‐resistant cell lines and in vivo models . Cabazitaxel, which is the 7,10 dimethyloxy derivative of docetaxel, demonstrates greater activity than docetaxel in multiple adult solid tumor models with inate or acquired taxane resistance .…”
Section: Introductionmentioning
confidence: 99%
“…Cabazitaxel is a semisynthetic taxane that was identified through a large‐scale screening process designed to select agents that show consistent activity in both docetaxel‐sensitive and docetaxel‐resistant cell lines and in vivo models . Cabazitaxel, which is the 7,10 dimethyloxy derivative of docetaxel, demonstrates greater activity than docetaxel in multiple adult solid tumor models with inate or acquired taxane resistance .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, cabazitaxel showed high permeability in cells expressing high levels of P‐gp, and higher intracellular accumulation than first‐generation taxanes in multidrug‐resistant ABCB1 (+) cell lines . Cabazitaxel penetrates BBB both in non‐tumor bearing and orthotopic glioma models, with similar exposure patterns observed in mice, rats and dogs …”
Section: Introductionmentioning
confidence: 79%
“…Preclinical evaluation suggested that cabazitaxel may be able to penetrate the BBB, providing rationale for the evaluation of cabazitaxel in pediatric patients with CNS tumors . In the phase 1 study, cabazitaxel was assessed in pediatric patients with recurrent/refractory solid tumors, including CNS tumors.…”
Section: Discussionmentioning
confidence: 99%
“…As Figure 1A shows, CTX had higher solubility in F127, up to 6 mg mL −1 , compared to DTX and PTX (1 mg mL −1 and 2 mg mL −1 , respectively). This may stem from the somewhat higher lipophilicity of CTX compared to other taxanes (CTX has a log P partition coefficient of 3.7, whereas DTX has a log P of 2.6, and PTX has a log P of 3.2) …”
Section: Resultsmentioning
confidence: 99%
“…The main mechanism of the action of CTX is to stabilize the tubulin polymerization, leading to cellular apoptosis . Microtubule polymerization was evaluated using a porcine tubulin assay.…”
Section: Resultsmentioning
confidence: 99%